Erdheim-Chester disease presented with bilateral carotid artery occlusion: Case report - (:unkn) unknown (My University, 2010)
Erdheim-Chester disease is a rare, non-Langerhans form of systemic histiocytosis of unknown etiology. The disease affects multiple organ systems, including musculoskeletal, cardiac, pulmonary, gastrointestinal, and central nervous systems, producing protean manifestations. Neurological manifestations are less frequent. We present a 44-year-old patient with Erdheim-Chester disease who had bilateral carotid artery occlusion and cavernous sinus infiltration.
Keywords: Carotid arteries; Erdheim-Chester disease; Ophthalmoplegia